Economics and the Biologists: A Review of Geerat J. Vermeij's Nature: An Economic History - Mokyr, Joel (Journal of Economic Literature, 2006)
This essay reviews and criticizes Vermeij's Nature: An Economic History and places it in the context of evolutionary economics. Vermeij presents a natural history written in what he considers economic terms and argues that biologists should know more about economics. While the exchanges between economics and biology can sometimes be hazardous and misleading, quite a bit could be learned by economists from reading this book.